Effects of impaired steryl ester biosynthesis on tomato growth and developmental processes - Burciaga-Monge, Alma; López-Tubau, Joan Manel; Laibach, Natalie; Deng, Cuiyun; Ferrer, Albert; Altabella, Teresa (Frontiers in Plant Science, 2022)
Steryl esters (SE) are stored in cytoplasmic lipid droplets and serve as a reservoir of sterols that helps to maintain free sterols (FS) homeostasis in cell membranes throughout plant growth and development, and provides the FS needed to meet the high demand of these key plasma membrane components during rapid plant organ growth and expansion. SE are also involved in the recycling of sterols and fatty acids released from membranes during plant tissues senescence. SE are synthesized by sterol acyltransferases, which catalyze the transfer of long-chain fatty acid groups to the hydroxyl group at C3 position of FS. Depending on the donor substrate, these enzymes are called acyl-CoA:sterol acyltransferases (ASAT), when the substrate is a long-chain acyl-CoA, and phospholipid:sterol acyltransferases (PSAT), which use a phospholipid as a donor substrate. We have recently identified and preliminary characterized the tomato (Solanum lycopersicum cv, Micro-Tom) SlASAT1 and SlPSAT1 enzymes. To gain further insight into the biological role of these enzymes and SE biosynthesis in tomato, we generated and characterized CRISPR/Cas9 single knock-out mutants lacking SlPSAT1 (slpsat1) and SlASAT1 (slasat1), as well as the double mutant slpsat1 x slasat1. Analysis of FS and SE profiles in seeds and leaves of the single and double mutants revealed a strong depletion of SE in slpsat1, that was even more pronounced in the slpsat1 x slasat1 mutant, while an increase of SE levels was observed in slasat1. Moreover, SlPSAT1 and SlASAT1 inactivation affected in different ways several important cellular and physiological processes, like leaf lipid bodies formation, seed germination speed, leaf senescence, and the plant size. Altogether, our results indicate that SlPSAT1 has a predominant role in tomato SE biosynthesis while SlASAT1 would mainly regulate the flux of the sterol pathway. It is also worth to mention that some of the metabolic and physiological responses in the tomato mutants lacking functional SlPSAT1 or SlASAT1 are different from those previously reported in Arabidopsis, being remarkable the synergistic effect of SlASAT1 inactivation in the absence of a functional SlPSAT1 on the early germination and premature senescence phenotypes